The kinesin KIF3AC recycles endocytosed integrin to polarize new adhesion formation toward the leading edge - Johnny A. Z. Rockenbach; Guilherme P. F. Nader; Susumu Antoku; Gregg G. Gundersen (Proceedings of the National Academy of Sciences, 2025)
The recycling of integrin endocytosed during focal adhesion (FA) disassembly is critical for cell migration and contributes to the polarized formation of new FAs toward the leading edge. How this occurs is unclear. Here, we sought to identify the kinesin motor protein(s) that is involved in recycling endocytosed integrin back to the plasma membrane. We show that the kinesin-2 heterodimer, KIF3AC, and the Rab11 adaptor protein Rab coupling protein (RCP) are required for FA reformation after the disassembly of FAs in mouse and human fibroblasts. In the absence of KIF3AC, integrin does not return to the cell surface after FA disassembly and is found in the Rab11 endocytic recycling compartment. Biochemical pulldowns revealed that KIF3C associated with β1 integrin in an RCP-dependent fashion, but only after FA disassembly. KIF3AC knockdown inhibited cell migration, trafficking of RCP toward the leading edge, and polarized formation of FAs at the leading edge. These results show that KIF3AC promotes cell migration by recycling integrin so that it generates new FAs in a polarized fashion.